Characteristics of patients with secondary erythrocytosis in relation to patients with polycythemia vera - Jeremić, Milica (Srpski medicinski časopis Lekarske komore, 2021)
Introduction: Erythrocytosis presents elevated hemoglobin and hematocrit levels above the range of normal values. Primary erythrocytosis is characterized by increased erythrocyte production due to disorder at the level of the multipotent stem cell in bone marrow. Diversely, secondary erythrocytosis (SE) is due to bone marrow stimulation by external factor. Aim: The aim of our study was to determine parameters which are significant to differentiate SE from primary erythrocytosis (PV). Material and methods: This is a retrospective study involving 108 patients with SE and 111 patients with PV who were diagnosed and treated at the Clinic of Hematology, UCCS (december 2005-november 2018). From the patient record following data were extracted: demographic characteristics, laboratory parameters, spleen size, total red cell mass, serum EPO level, and spontaneus growth of BFU-E colony. Results: Patients with SE were younger with predominance of male gender with significantly higher serum EPO ​​than in patients with PV. Patients with PV had significantly higher values of BFU-E, and count of leukocytes, platelets, spleen size, level of LDH ​​than patients with SE. Total red cell mass analysis did not show a differential diagnostic significance. Conclusion: In patients, findings of normal spleen size, normal leukocyte and platelet count, normal serum LDH, and elevated EPO refer to the diagnosis of secondary erythrocytosis, while the findings of splenomegaly, leukocytosis, thrombocytosis, elevated serum LDH, and decreased EPO favor the diagnosis of polycythemia vera.